Optimization of the Role of Health Cadres in Educating About the Integration of Primary Services for the Prevention and Control of Non-Communicable Diseases in Tropical Regions - Sumarni Sumarni; Muhamad Zakki Saefurrohim; Muh. Amri Arfandi (Mulawarman International Conference on Tropical Public Health, 2025)
Pasundan Public Health Center ranks among the top three areas with the highest prevalence of Non- Communicable Diseases (NCDs) in Samarinda City, with 23.2% hypertension and 2.95% diabetes mellitus cases. The main challenge lies in the suboptimal role of health cadres in implementing the Integrated Primary Care (ILP) program and their limited digital health literacy. This issue highlights a practical and scientific gap in the effective utilization of health cadres for NCD prevention and control through technology-based health education. To optimize the role of health cadres in the implementation of ILP by improving their knowledge, communication, and digital literacy skills for NCD prevention and control in tropical regions. The program was implemented through community service activities, including socialization, health education, and practical demonstrations involving 37 health cadres from 35 integrated health posts. Evaluation of outcomes was conducted using interactive pre–post tests and participant feedback to measure improvements in knowledge and skills. The evaluation showed a significant increase in cadres’ knowledge from 68% to 89%, along with an improvement in communication and digital literacy skills by 35–40%. The training enhanced cadres’ confidence and ability to utilize digital platforms in disseminating health information related to NCD prevention and control. The program successfully strengthened the capacity of health cadres in technology-based health promotion, supporting the sustainability and effectiveness of Integrated Primary Care at the primary healthcare level. Enhancing digital literacy among cadres is crucial for improving NCD prevention and control efforts in tropical regions.